JILBAB DALAM HADIS: Menelusuri Makna Profetik dari Hadis - Marhumah, Ema (Musawa Jurnal Studi Gender dan Islam, 2014)
Nowadays the meaning of the jilbab has shifted and become somewhat misinterpreted. Understandings of the purpose of the jilbab began with Tauhid, the principle teaching of Islam. The Tauhid teaches the true meaning of devotion to God or godliness, and also the true meaning of how to be human. The Tauhid teachings bring about recognition of sameness before God, and the obligation to respect other people without discrimination based on differences in sex, gender, ethnicity or religion. In Indonesia, the jilbab is not only worn as a form of identity but as a fashion accessory. It is not clear whether the use of the terms jilbab or hijab are to be interpreted as head coverings to the chest for women or not. For this reason, there is a need for a comprehensive understanding of the terms to be taken from a holy book, in this case the Al’Qur’an and hadis, so that there is no longer a distortion in meaning. A full understanding of the verses and hadis in relation to the jilbab and the hijab is not limited to symbolic use. Whether of not the use of the veil is merely symbolic, it must be considered in the current context of the rise of capitalist religiosity.